False Dichotomy: Building Awareness of Mass and Interpersonal Communication Convergence in the Era of Digital Technology in Indonesia - Prahastiwi Utari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
This paper is written as input for managers of higher education in Communication Studies in regards to the phenomenon of new digital communication technology development, as well as communication theory and research in Indonesia. While many communication scientists outside Indonesia have been talking about the importance of unifying the realms of mass and interpersonal communication theories in the era of digital technology, the teaching of communication theory in Indonesia has not accommodated such convergence. This has resulted in the absence of new/digital communication technologies in the existing communication research. Using the historical perspectives and previous works of communication scientists, a new perspective in the teaching of communication theory can be formulated, one that unifies the boundaries between mass and interpersonal communication. In addition, communication research that considers the presence of new communication technologies should also be pursued.